The prevalence of genetic variants of the Mas-related G-protein-coupled receptor X2 in patients does not explain perioperative hypersensitivity reactions to neuromuscular blocking agents - Dziadowiec, Alicja; Kwitniewski, Mateusz; Kopac, Peter; Rybka, Hubert; Sedlackova, Lenka; Srotova, Adriana; Dyga, Wojciech; Koren, Ana; Gluck, Joanna; Kitel, Radoslaw; Porebski, Grzegorz (Frontiers in Pharmacology, 2025)
BackgroundNeuromuscular blocking agents (NMBAs) may induce life-threatening perioperative hypersensitivity reactions (POH). In addition to the known IgE-dependent allergic background, a mechanism dependent on Mas-Related G Protein-Coupled Receptor-X2 (MRGPRX2) on mast cells has been postulated. This does not explain why NMBA-induced POH is sporadic and only occurs in some patients. We hypothesised that this phenomenon depends on single nucleotide polymorphisms (SNPs) in MRGPRX2 that enhance the response to NMBA.MethodsThe protein coding sequence of the MRGPRX2 gene was sequenced in 31 patients with NMBA-induced POH and 42 controls. Medical history and skin tests were used to diagnose patients. Based on basophil activation test (BAT) and specific IgE, patients were classified as having a history of IgE-mediated or likely MRGPRX2-mediated reactions. Severity of POH was defined according to a commonly accepted scale. Molecular dynamics simulations were conducted to assess the functional and structural effects of the SNPs.ResultsThe most common causative drugs were rocuronium (n = 17) and atracurium (n = 7), the others were cisatracurium, vecuronium, suxamethonium (n = 2 each) and pipecuronium (n = 1). We detected one missense SNP: N62S, present in 38.7% of the study group and in 45.2% of the controls. Prevalence of this SNP in patients was not dependent on causative drug, BAT and sIgE results, or severity of POH or its skin manifestations. Analysis of root mean square deviation and fluctuation plots showed no significant differences between wild-type and N62S variants.ConclusionSNPs detected within the protein coding sequence of the MRGPRX2 gene were not risk factor in NMBA-induced POH, regardless of the clinical characteristics of the patients and the causative drug in question.